Dienstleistungen im digitalen Zeitalter. Dort sein, wo die Nutzer sind. - Askey, Dale (My University, 2010)
Posits that the five laws of library science propagated by Ranganathan have mutated over the years, leading to dysfunction in our relations with users.
Keywords: Libraries; Services; Ranganathan; Laws